Microglia in Alzheimer's Disease: A Role for Ion Channels - Thei, Laura; Imm, Jennifer; Kaisis, Eleni; Dallas, Mark L.; Kerrigan, Talitha L. (Frontiers in Neuroscience, 2018)
Alzheimer’s disease is the most common form of dementia, it is estimated to affect over 40 million people worldwide. Classically, the disease has been characterised by the neuropathological hallmarks of aggregated extracellular amyloid-β and intracellular paired helical filaments of hyperphosphorylated tau. A wealth of evidence indicates a pivotal role for the innate immune system, such as microglia, and inflammation in the pathology of Alzheimer’s disease. The over production and aggregation of Alzheimer’s associated proteins results in chronic inflammation and disrupts microglial clearance of these depositions. Despite being non-excitable, microglia express a diverse array of ion channels which shape their physiological functions. In support of this, there is a growing body of evidence pointing to the involvement of microglial ion channels contributing to neurodegenerative diseases such as Alzheimer’s disease. In this review, we discuss the evidence for an array of microglia ion channels and their importance in modulating microglial homeostasis and how this process could be disrupted in Alzheimer’s disease. One promising avenue for assessing the role that microglia play in the initiation and progression of Alzheimer’s disease is through using induced pluripotent stem cell derived microglia. Here, we examine what is already understood in terms of the molecular underpinnings of inflammation in Alzheimer’s disease, and the utility that inducible pluripotent stem cell derived microglia may have to advance this knowledge. We outline the variability that occurs between the use of animal and human models with regards to the importance of microglial ion channels in generating a relevant functional model of brain inflammation. Overcoming these hurdles will be pivotal in order to develop new drug targets and progress our understanding of the pathological mechanisms involved in Alzheimer’s disease.